Feasibility and Acceptability of ACT for the Community Case Management of Malaria in Urban Settings in Five African Sites - Akweongo, P.; Agyei-Baffour, P.; Sudhakar, M.; Simwaka, B. N.; Konate, A. T.; Adongo, P. B.; Browne, E. N.; Tegegn, A.; Ali, D.; Traore, A.; Amuyunzu-Nyamongo, M.; Pagnoni, F.; et al. (2012)
The community case management of malaria (CCMm) is now an established route for distribution of artemisinin-based combination therapy (ACT) in rural areas, but the feasibility and acceptability of the approach through community medicine distributors (CMD) in urban areas has not been explored. It is estimated that in 15 years time 50% of the African population will live in urban areas and transmission of the malaria parasite occurs in these densely populated areas. METHODS: Pre- and post-implementation studies were conducted in five African cities: Ghana, Burkina Faso, Ethiopia and Malawi. CMDs were trained to educate caregivers, diagnose and treat malaria cases in < 5-year olds with ACT. Household surveys, focus group discussions and in-depth interviews were used to evaluate impact. RESULTS: Qualitative findings: In all sites, interviews revealed that caregivers' knowledge of malaria signs and symptoms improved after the intervention. Preference for CMDs as preferred providers for malaria increased in all sites.Quantitative findings: 9001 children with an episode of fever were treated by 199 CMDs in the five study sites. Results from the CHWs registers show that of these, 6974 were treated with an ACT and 6933 (99%) were prescribed the correct dose for their age. Fifty-four percent of the 3,025 children for which information about the promptness of treatment was available were treated within 24 hours from the onset of symptoms.From the household survey 3700 children were identified who had an episode of fever during the preceding two weeks. 1480 (40%) of them sought treatment from a CMD and 1213 of them (82%) had received an ACT. Of these, 1123 (92.6%) were administered the ACT for the correct number of doses and days; 773 of the 1118 (69.1%) children for which information about the promptness of treatment was available were treated within 24 hours from onset of symptoms, and 768 (68.7%) were treated promptly and correctly. CONCLUSIONS: The concept of CCMm in an urban environment was positive, and caregivers were generally satisfied with the services. Quality of services delivered by CMDs and adherence by caregivers are similar to those seen in rural CCMm settings. The proportion of cases seen by CMDs, however, tended to be lower than was generally seen in rural CCMm. Urban CCMm is feasible, but it struggles against other sources of established healthcare providers. Innovation is required by everyone to make it viable.